Requiem for a Dream: Perceived Economic Conditions and Subjective Well-Being in Times of Prosperity and Economic Crisis - Fernandez-Urbano, Roger (Soc Indic Res, 2020)
Using the Panel of Social Inequalities in Catalonia, Spain (PaD 2001–2012), this article investigates the relationship between perceptions of economic conditions and subjective well-being in times of prosperity and economic crisis. It also analyses how this relationship plays out across different social backgrounds. Periods of economic crisis and prosperity serve as a proxy for objective macroeconomic conditions. The Spanish region of Catalonia is a relevant setting because it faced one of the highest increases in inequality and unemployment in Europe as a result of the 2008 Economic Crisis. Our results show that perceived economic conditions matter beyond objective micro and macroeconomic realm and become a strong determinant of subjective well-being during a crisis, particularly for the middle class. However, contrary to our initial expectations, our results also show the existence of a close correlation between perceptions of economic conditions and subjective well-being for low social background individuals in times of economic prosperity, and an even stronger relationship in times of economic crisis. The article stipulates several potential explanations for these results.